2023
DOI: 10.1038/s42004-023-00884-8
|View full text |Cite
|
Sign up to set email alerts
|

Mirror proteorhodopsins

Abstract: Proteorhodopsins (PRs), bacterial light-driven outward proton pumps comprise the first discovered and largest family of rhodopsins, they play a significant role in life on the Earth. A big remaining mystery was that up-to-date there was no described bacterial rhodopsins pumping protons at acidic pH despite the fact that bacteria live in different pH environment. Here we describe conceptually new bacterial rhodopsins which are operating as outward proton pumps at acidic pH. A comprehensive function-structure st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 148 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…However, recent works showed that there are other positions in MRs, which co-determine the function of the protein and might differ between the clades of a given family. An example is the position of T46 in the helix B of BR, which can be occupied by glutamic acid in viral rhodopsins of groups 1 and 2 10,11 or histidine in bacterial outward proton pumps 12,13 and is actively involved in the ion translocation process.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent works showed that there are other positions in MRs, which co-determine the function of the protein and might differ between the clades of a given family. An example is the position of T46 in the helix B of BR, which can be occupied by glutamic acid in viral rhodopsins of groups 1 and 2 10,11 or histidine in bacterial outward proton pumps 12,13 and is actively involved in the ion translocation process.…”
Section: Introductionmentioning
confidence: 99%